A Unique Case of Mycophenolate Induced Colitis after 10 Years of Use - Abhinav Goyal; Moiz Salahuddin; Yogesh Govil (Case Reports in Gastrointestinal Medicine)
A 31-year-old female with a history of lupus nephritis on Hydroxychloroquine, Prednisone, and Mycophenolate Mofetil (MMF) for 10 years presented to the hospital for ankle swelling. On day four, she started to have severe, nonbloody, watery diarrhea with abdominal distension and tenderness. Stool PCR was negative for C. difficile. CT abdomen/pelvis showed gaseous distension of the colon without any obstruction. Flexible sigmoidoscopy revealed a normal looking mucosa. Histopathology showed crypt atrophy and increased crypt apoptosis, consistent with MMF colitis. The diarrhea resolved three days after stopping MMF. Although generally well tolerated, diarrhea is a common side effect of MMF. Most cases occur in the first six months of starting MMF. This case is unique because it describes MMF colitis in lupus after more than 10 years. Thus, MMF colitis should be considered as a differential in patients taking it, regardless of the duration of use.